Inverse kinematics and workspace analysis of a novel SSRMS-type reconfigurable space manipulator with two lockable passive telescopic links. (February 2023) - Zhao, Jingdong; Zhao, Zhiyuan; Yang, Xiaohang; Zhao, Liangliang; Yang, Guocai; Liu, Hong
Highlights: A novel SSRMS-type self-reconfigurable space redundant manipulator. A new CCDJAP-IK method for solving the inverse kinematics (IK) problem. The IK problem of the redundant manipulator with multiple joint offsets is solved. Workspace analysis of the manipulator with two lockable passive telescopic links. An information-driven optimal configuration search method of the manipulator. Abstract: This study proposes a novel space station remote manipulator system (SSRMS)-type reconfigurable space manipulator to enhance the adaptability of the traditional SSRMS-type manipulators in complex on-orbit tasks. The proposed manipulator has two lockable passive telescopic links (LPTLs) and allows changing their lengths to achieve reconfigurability. The inverse kinematics (IK) and the workspace for this manipulator are minutely analyzed. We develop a new CCDJAP-IK method to solve the IK problem by combining the cyclic coordinate descent (CCD) and joint angle parameterization (JAP) methods. This new method addresses the CCD method's convergence instability and the JAP method's high dependence on the pre-set value of the redundancy parameter. In particular, our approach is insensitive to the initial and singular configurations and can generate multiple exact solutions that satisfy the joint limit constraints. A reachability sphere map captures the proposed manipulator's kinematic capability for the workspace analysis. Then the effects of the two LPTLs on this capability are deeply explored. Based on the results, we propose an information-driven optimal configuration search method. Several typical simulations validate the proposed methods' effectiveness.